2011
DOI: 10.1111/j.1523-5378.2011.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Analysis of Early-Stage Gastric Cancers Detected After Successful Eradication of Helicobacter pylori

Abstract: Our findings indicate that the clinicopathological characteristics of gastric cancers detected after H. pylori eradication are different from those of gastric cancers in patients with persistent H. pylori infection. H. pylori eradication may suppress intestinalization during the development of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
100
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(110 citation statements)
references
References 23 publications
(39 reference statements)
9
100
0
1
Order By: Relevance
“…However, gastric cancer is discovered in patients even after successful H. pylori eradication [5]. Moreover, H. pylori eradication influences the clinicopathological features of gastric tumors, including macro-and microscopic appearances [6][7][8][9][10]. Gastric cancer found after H. pylori eradication appears with indistinct forms, such as tiny and flattened lesions [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, gastric cancer is discovered in patients even after successful H. pylori eradication [5]. Moreover, H. pylori eradication influences the clinicopathological features of gastric tumors, including macro-and microscopic appearances [6][7][8][9][10]. Gastric cancer found after H. pylori eradication appears with indistinct forms, such as tiny and flattened lesions [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer incidence after H. pylori eradication is increasing recently, but it is difficult to find it because of its ambiguity. [14]. Our result might provide more appropriate clinical implementation for gastric cancer surveillance after eradication, reflecting individual cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…The data also demonstrated that the therapy could reverse the hypermethylation in certain genes [11,12]. Even after successful H. pylori eradication, on the other hand, gastric cancers are sometimes identified [13,14]. The residual methylation in gastric mucosa after eradication might be relevant to this process [12,15].…”
Section: Introductionmentioning
confidence: 88%
“…Including the reports by Yamamoto et al [1] and Matsuo et al [2], [10 studies of GC detected after Hp eradication have been published to date [3][4][5][6][7][8][9][10]. The characteristics of post-eradication GC include: (a) detection *40 months after eradication; (b) lesions are histologically well differentiated; (c) gross lesion morphology is depressed; and (d) the lesions are small (10-20 mm diameter).…”
mentioning
confidence: 99%
“…The characteristics of post-eradication GC include: (a) detection *40 months after eradication; (b) lesions are histologically well differentiated; (c) gross lesion morphology is depressed; and (d) the lesions are small (10-20 mm diameter). Pathologically, the Ki-67 index and Wnt5a expression are significantly reduced [1,11]. In some patients, the mucosa surrounding the lesion is obscured [11], possibly due to the flattening of the tumor tissue, with formation of non-neoplastic foveolar epithelium as the outermost layer.…”
mentioning
confidence: 99%